LC3-associated phagocytosis in myeloid cells, a fireman that restrains inflammation and liver fibrosis, via immunoreceptor inhibitory signaling. Issue 8 (2nd August 2020) - Wan, JingHong; Weiss, Emmanuel; Ben Mkaddem, Sanae; Mabire, Morgane; Choinier, Pierre-Marie; Thibault-Sogorb, Tristan; Hegde, Pushpa; Bens, Marcelle; Broer, Linda; Gilgenkrantz, Hélène; Moreau, Richard; Saveanu, Loredana; et al.
ABSTRACT: Control of systemic and hepatic inflammation, in particular originating from monocytes/macrophages, is crucial to prevent liver fibrosis and its progression to end-stage cirrhosis. LC3-associated phagocytosis (LAP) is a non-canonical form of autophagy that shifts the monocyte/macrophage phenotype to an anti-inflammatory phenotype. In a recent study, we uncovered LAP as a protective mechanism against inflammation-driven liver fibrosis and systemic inflammation in the context of cirrhosis. We observed that LAP is enhanced in blood and liver monocytes from patients with liver fibrosis or those who progress to cirrhosis. Combining studies in which LAP was pharmacologically or genetically inactivated, we found that LAP limits inflammation in monocytes from cirrhotic patients, and the hepatic inflammatory profile in mice with chronic liver injury, resulting in anti-fibrogenic effects. Mechanistically, LAP-induced anti-inflammatory and antifibrogenic signaling results from enhanced expression of the Fc immunoreceptor FCGR2A/FcγRIIA and activation of an FCGR2A-mediated PTPN6/SHP-1 anti-inflammatory pathway, leading to increased engulfment of IgG into LC3 + phagosomes. In patients with cirrhosis progressing to multi-organ failure (acute-on chronic liver failure), LAP is lost in monocytes, and can be restored by targeting FCGR2A-mediated PTPN6/SHP-1 signaling. These data suggest that sustaining LAP may open novel therapeutic perspectives for patients with end-stage liver disease.